Wild bonobos host geographically restricted malaria parasites including a putative new Laverania species. Issue 1 (December 2017) - Liu, Weimin; Sherrill-Mix, Scott; Learn, Gerald; Scully, Erik; Li, Yingying; Avitto, Alexa; Loy, Dorothy; Lauder, Abigail; Sundararaman, Sesh; Plenderleith, Lindsey; Ndjango, Jean-Bosco; Georgiev, Alexander; et al.
Abstract Malaria parasites, though widespread among wild chimpanzees and gorillas, have not been detected in bonobos. Here, we show that wild-living bonobos are endemicallyPlasmodium infected in the eastern-most part of their range. Testing 1556 faecal samples from 11 field sites, we identify high prevalenceLaverania infections in the Tshuapa-Lomami-Lualaba (TL2) area, but not at other locations across the Congo. TL2 bonobos harbourP. gaboni, formerly only found in chimpanzees, as well as a potential new species, Plasmodium lomamiensis sp. nov. Rare co-infections with non-Laverania parasites were also observed. Phylogenetic relationships amongLaverania species are consistent with co-divergence with their gorilla, chimpanzee and bonobo hosts, suggesting a timescale for their evolution. The absence ofPlasmodium from most field sites could not be explained by parasite seasonality, nor by bonobo population structure, diet or gut microbiota. Thus, the geographic restriction of bonoboPlasmodium reflects still unidentified factors that likely influence parasite transmission. Unlike chimpanzees and gorillas, bonobos have not been found infected by malaria parasites in the wild. Here, Liu et al. report more thorough survey and sequencing results showing that bonobos host malaria parasites, including a yet-unknown species, but only in the eastern-most part of their range.